If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 5(4 + 6n) = 107 -3 + (4 * 5 + 6n * 5) = 107 -3 + (20 + 30n) = 107 Combine like terms: -3 + 20 = 17 17 + 30n = 107 Solving 17 + 30n = 107 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 30n = 107 + -17 Combine like terms: 17 + -17 = 0 0 + 30n = 107 + -17 30n = 107 + -17 Combine like terms: 107 + -17 = 90 30n = 90 Divide each side by '30'. n = 3 Simplifying n = 3
| 4-6(k+7)=5k+17 | | p-6=3(p-4) | | 8+6(t+2)=32 | | 8-6m=26 | | 8m-7(3-5m)=280 | | -12-2k=-2(k+4) | | x+135+20=x+35 | | 3(x+6)=221 | | x+40+2x-10=180 | | 1.4b+10=18 | | 34+8m=6(3m+1)-3m | | -4(2x-1)=2(3x+2)-14x | | 2a-6+5a=3-a+7 | | 3+7(-3n+6)=-4n-6 | | -6(z-2)=3 | | 17+(-3x)=14 | | 2x-10-7x=3(x-6) | | 6(7-6n)=114 | | 7(5x-4)=5+2x | | n^2+(-3)(4)=28 | | 17+(-3)=14 | | 5+X=-36 | | 2y+7=35 | | h=16t^2+52t+16 | | 4.95+11.95=64.70 | | 40+2m=-8(m+5) | | x+74+36=77 | | 5(x-3)-4(x-3)=3(x-1) | | 2x^4-10x^2+5=0 | | 10t^2-17t+6=0 | | -4w+8=-8(w+3) | | 0.23*50=1*x |